Age-Related Changes in Depth Perception through Shape-from-Shading - Broadbent, H.E. (2024)
The primary objective of this thesis was to explore the sensitivity of perception of shape-from-shading. Concurrently, age-related perceptual and cognitive function were also investigated to determine how these changes contribute to the sensitivity to shape-fromshading cues. The human visual system operates through different mechanisms capable of perceiving and interpreting information from the surrounding environment. This chapter reviews the literature on first- and second-order vision, emphasising studies investigating shape-from-shading. First, the origins of shape-from-shading observed in natural scenes are discussed alongside our understanding of the interaction between first- and second-order vision in depth perception. First- and second-order vision principles are then discussed, and models of processing that seek to further our understanding of this association are presented. Lastly, the impact of ageing on visual sensitivity of first- and second-order processing is discussed, along with research corroborating both visual and neural contributions to age-related alterations in the visual system.